Selected Saturated Chlorinated Hydrocarbons and Their Properties in Relationship of Resistance of Butyl-Rubber Polymeric Materials - Otřísal, Pavel; Florus, Stanislav (International Journal of Advances in Life Science and Technology, 2014)
The article describes how to test isolative resistance times of the protective folio based on a polyamide carrier fabric coating with butyl-rubber polymer mixture measured by the linear substituted saturated chlorinated aliphatic hydrocarbons. Information about quality of means of isolative protection is very important. Their availability may be limited, and therefore, in some cases will need to rely on the value of breakthrough times for basic hydrides of hydrocarbons, which are not substituted.